Paradigma usul fikih multikultural di Indonesia - Dahlan, Moh (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2012)
This study aims to examine how the significance of multicultural paradigm of usul fiqh in social and national life which is diversity. Approach to study uses a paradigm shift in Kuhnâs opinion and theoritical framework of this study uses a âstatic and dynamic multiculturalityâ in Baidoeriâs opinion. The results of this study indicated that the diversity of life and religion of this nation need paradigms of multicultural opinion to create social and national life which are quiet, peaceful, tolerant as well as mutual respect and cooperation. As the largest Muslim nation, Muslims of Indonesia should have a multicultural paradigm of us}u>l fiqh to build a fiqh opinion which is tolerant and accommodating towards differences and diversity of socio-culture, politics and religion, rather than monocultural paradigm of ushul fiqh that aims to formalize the Islamic jurisprudence that is exclusive and discriminatory.